Tahap latihan, pengetahuan dan keyakinan guru-guru pendidikan khas tentang autisme - Hasnah Toran,; Mohd. Hanafi Mohd. Yasin,; Mohd. Mokhtar Tahar,; Norani Salleh, (penerbit ukm, 2010)
Autism is a developmental disorder that negatively impacts the ability for communication and interaction. Current statistics have reported an increase in its prevalence. Therefore, the need for well trained teachers to teach children with autism has also increased. This study was implemented to investigate the level of training, knowledge, and confidence of special education teachers on autism. Formal teacher training courses was found to be rather ineffective in training special education teachers to understand and teach children with autism. It has also been found that inservice training is slightly better in quality. This caused them to have low confidence in their ability to teach children with autism. However, they showed interest to undergo advanced courses to enhance their competence in educating children with autism. Therefore, formal special education teacher training needs to be improved through an additional component on autism. Special education teachers also need to be provided with access to inservice training in autism because the field of autism education has progressed and various strategies that have been proven effective scientifically are now available. Further studies are needed to identify weaknesses in both types of teacher training and methods to improve the quality of both in terms on education for children with autism.